THE ECOLOGICAL CONSUMER LIKE SOURCE OF COMPETITIVE ADVANTAGE AND HIS IMPACT IN THE IDENTIFICATION OF STRATEGIC BUSINESS OPPORTUNITIES IN THE REGION OF TULA-TEPEJI OF THE HIDALGO STATE - Tirso Javier Hernandez Gracia; Dolores Margarita Navarrete Zorrilla; Garcia del Rosario Velazquez; Jose Francisco Hernández Gracia; Juan Alberto Carranza Sevilla; Alejandro Justo Lugo; Alejandra Corichi Garcia (European Scientific Journal, ESJ, 2014)
The Group of Regional Development of the Monterrey's Technological one approached to integrating the Megatrends that in the opinion of his investigators probably will mark the predictable future of the world, both in the technological aspect and in the social one, trying to identify the behaviors that will influence to persons, groups, institutions, communities, regions and countries, for with it to identify opportunities of products and emergent services that could be commercialized on the world markets. Such it is the case of the ecological consumer who presents a few specific features that are precise to know, in order to be able to propose commercial solutions that adjust to his requirements. Giving continuity to this interesting topic of investigation, in the present project across one of the most important tools of the marketing like it it is the investigation of markets it was deciding, the knowledge, managing, application and impact of the ecological consumer, which use as base for the development and sustentabilidad as the business in the region of Tula-Tepeji, of the Hidalgo State.